Photocatalytic Degradation of Metronidazole Using Zinc Oxide Nanoparticles Supported on Acha Waste - Olushola Sunday Ayanda; Blessing Oluwatobi Adeleye; Omolola Helen Aremu; Folasade Busayo Ojobola; Olayide Samuel Lawal; Olusola Solomon Amodu; Oyedele Oyebamiji Oketayo; Michael John Klink; Simphiwe Maurice Nelana (Indonesian Journal of Chemistry, 2023)
The presence of emerging pollutants like pharmaceutical compounds in the environment is currently an issue of concern. Pharmaceutical compounds often escape conventional treatment systems and are persistent in the receiving environment; thus, the advanced oxidation processes could complement existing treatment methods to completely remove pharmaceuticals from contaminated water bodies. This work investigated the removal of metronidazole by ultra-violet light catalyzed by zinc oxide nanoparticles supported on acha waste. The synthesized zinc oxide nanoparticles, acha waste, and zinc oxide nanoparticles/acha waste composite were characterized by electron microscopy (SEM and TEM), Fourier transforms infrared spectrometry (FTIR) and X-ray diffractometry (XRD). Experimental results revealed that the UV light combined with zinc oxide nanoparticles and/or acha waste was more effective for metronidazole removal in combination than UV alone. The degradation of the metronidazole by UV light only, UV/nano-ZnO, and UV/nano-ZnO/acha waste systems follow the pseudo-first-order kinetic model. The addition of a catalyst to the UV reactor enhanced the degradation of metronidazole (5 mg/L) from 41.0 up to 86.1%. The outcome of this research showed that UV light in the presence of nanometal oxides and composites is an efficient technique for the removal of pharmaceuticals from an aqueous solution.